Avaliação de áreas vulneráveis a movimento de massa na cidade de João Pessoa – PB - Lima, Laís Costa (2019)
Mass movement is a natural and transformative process in the relief of a region. However, when these phenomena occur in occupied areas, they become dangerous to society. The intensification of urbanized areas, the rural exodus and the need for housing by the population with the lowest purchasing power in large cities has become a fact in the process of growth of cities in contemporary society, which has forced this population to establish their homes in areas with no housing conditions. These people are more likely to suffer losses from natural disasters, due to their vulnerable situation. In addition to the high number of fatalities, mass movements can also cause significant socioeconomic damage. Despite of the fact that humanity is facing these adversities is not new, and that historically many natural disasters have been recorded throughout history, the preventive reaction to these events is still a challenge for society. As the important function of subsidizing risk management processes, slope stability analysis is an important tool in urban areas. In the city of João Pessoa there are 48 areas susceptible to mass movement problems. In this context, this paper presents a risk analysis carried out on a sample consisting of the communities Ari Barroso, Saturnino de Brito, Terra do Nunca, Minervino Bione and Santa Clara. A drone, was used to map the areas. Mass movement risk assessment models were applied to determine safety coefficients and to evaluate the geological risks related to the collapse of hillsides, classifying them. The results showed geological risks classified as High to Very High in 4 of the studied communities and Medium in the Minervino Bione community. With the exception of the Ari Barroso Community, in which the safety factor indicated risks ranging from High to Very High.